A pyridinium/anilinium [2]catenane that operates as an acid–base driven optical switch - Vella, Sarah J.; Loeb, Stephen J. (Beilstein Journal of Organic Chemistry, 2018)
A two-station [2]catenane containing a large macrocycle with two different recognition sites, one bis(pyridinium)ethane and one benzylanilinium, as well as a smaller DB24C8 ring was synthesized and characterized. 1H NMR spectroscopy showed that the DB24C8 ring can shuttle between the two recognition sites depending on the protonation state of the larger macrocycle. When the aniline group is neutral, the DB24C8 ring resides solely at the bis(pyridinium)ethane site, while addition of acid forms a charged benzylanilinium site. The DB24C8 then shuttles between the two charged recognition sites with occupancy favoring the bis(pyridinium)ethane site by a ratio of 4:1. The unprotonated [2]catenane has a deep yellow/orange color when the DB24C8 ring resides solely at the bis(pyridinium)ethane site and changes to colorless when the crown ether is shuttling (i.e., circumrotating) back and forth between the two recognition sites thus optically signalling the onset of the shuttling dynamics.
Keywords: catenane; mechanically interlocked molecule; molecular switch